Categorizing and qualifying nutritional lipidomic data: defining brutto, medio, genio, and infinio lipid species within macrolipidomics and microlipidomics. Issue 5 (September 2018) - Aristizabal Henao, Juan J.; Bradley, Ryan M.; Duncan, Robin E.; Stark, Ken D.
Abstract : Purpose of review: Lipidomic profiling of biological samples is increasing in nutritional research applications. 'Lipidomic analyses' however can be quite variable in specific methods and the type of information about the specific lipids that is revealed. The lack of defined and simple terminology to describe aspects of lipidomics presents a challenge in the use of lipidomics across interdisciplinary research groups. Recent findings: We propose the use of macrolipidomics and microlipidomics to define lipidomic strategies based on analytical outcomes. Macrolipidomics involves the global characterization of the most abundant lipids in a system, whereas microlipidomics examines low abundant lipids with potent bioactivity that typically require specialized analyses. We also propose that in addition to the term 'brutto', the terms 'medio, genio, and infinio' be used to indicate when information about the lipid molecule increases from isobars/isomers to regio-isomers with carbon–carbon double bond information. Summary: The use of these terms will help establish a common language around the field of lipidomics and improve communication and uptake in the field of clinical nutrition. Macrolipidomic and microlipidomic terms quickly convey the general purpose of the approach. Brutto, medio, genio, and infino quickly convey the nature of the lipid identification.